2018
DOI: 10.1007/s10965-018-1516-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of polyurethane foams prepared from liquefied sawdust by crude glycerol and polyethylene glycol

Abstract: The aim of this study was to investigate polyurethane foams (PUF) properties obtained from crude glycerol (CG) and polyethylene glycol (PEG) based liquefaction of sawdust. The four types of foam were prepared by producing polyols from different weight loadings of PEG to CG as the liquefaction solvent. The produced polyurethane foams showed densities from 0.042 to 0.08 g/cm 3 and compressive strengths from 200 to 311 kPa. The foams obtained from CG/PEG based liquefaction, had more uniform and regular cell struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…These results are also in agreement with the results reported in the literature for PU foams. 33 On the other hand, the important rise of the density by around 21% for the 40 wt.% AlN filled foam indicates a significant contribution of the density to the improvement of the thermal conductivity of the foams as reported in the literature. 29 Moreover, as the AlN fillers used in this study have a large particle size, we can deduce that when the filler content increases, the open cell content of the foams increases.…”
Section: Characterization Of Pu/aln Composite Foamsmentioning
confidence: 57%
See 1 more Smart Citation
“…These results are also in agreement with the results reported in the literature for PU foams. 33 On the other hand, the important rise of the density by around 21% for the 40 wt.% AlN filled foam indicates a significant contribution of the density to the improvement of the thermal conductivity of the foams as reported in the literature. 29 Moreover, as the AlN fillers used in this study have a large particle size, we can deduce that when the filler content increases, the open cell content of the foams increases.…”
Section: Characterization Of Pu/aln Composite Foamsmentioning
confidence: 57%
“…29 Moreover, as the AlN fillers used in this study have a large particle size, we can deduce that when the filler content increases, the open cell content of the foams increases. According to Rastegarfar et al, 33 when the open cell content increases, the thermal conductivity increases due to higher heat transfer in foam cells. This is also the case in our study where the thermal conductivity increases until a filler content of 10 wt.% and then almost stabilizes for foams with higher filler content.…”
Section: Characterization Of Pu/aln Composite Foamsmentioning
confidence: 98%
“…Due to the widespread applications of PUs, there is an intense focus to develop biobased and/or biodegradable PUs. 38 Biobased crude glycerol has been widely studied as the precursor for PUs, [39][40][41] even for specific applications such as thermal energy insulators, 42,43 waterborne films [44][45][46] and sound absorbers. 47 Crude glycerol is typically heated under vacuum at temperatures between 150-200°C for 2-5 h to synthesize polyols.…”
Section: Introductionmentioning
confidence: 99%
“…They can be recycled or recovered after use to reduce production costs and increase material utilization efficiency [3]. Thermosetting polymers like PU foams are widely preferred due to their light weight, excellent biocompatibility, flexible mechanical properties, and the presence of a urethane linkage (–NH–CO–O–) that bonds easily with nanoparticles such as silver nanoparticles (AgNPs) [4,5,6,7,8,9,10]. Also, PU foams have the capability of delivering a wide range of cell structures, rigidity, strength, and durability.…”
Section: Introductionmentioning
confidence: 99%
“…Abramoff et al [29] reported the determination of pore sizes, pore size distribution, and other pore morphologies using FIJI/ImageJ from scanning electron microscope micrographs and a JEOL Model JSM-6490. A study by Rastegarfar et al showed the characterization of PU foams produced from liquefied sawdust using SEM, among other techniques [8]. Bachtiar et al recently investigated the thermal stability and fire resistance of flax fabric-reinforced polymer composites with the help of SEM [30].…”
Section: Introductionmentioning
confidence: 99%